Comparative Histological Study of the Retina in the Eyes of two Fishes Silurus triostegus Heckel and Liza abu (Heckel): Iman S.A. Al-Jumaily ,*Abdol-Hakim A. Al-Rawi and **Mohamad A. Gali - Al-Jumaily, Iman S.A. (The Iraqi Journal of Veterinary Medicine, 2012)
The present Study Showed that the falciform process and vitereal vessels is extended upper to retina, which are found only in S. triostegus . The visual cells in both fishes have cones and rods with myoid element, myoids are inconspicuous in S. triostegus . The cones in S. triostegus are large but in L. abu found in four types, long single cones, short single cones, dwarf cones and twin cones. It appears that the cones in L. abu arranged as mosaic include square and row patterns, but they are distributed randomly in S. triostegus , also the cones in L. abu have lateral fins which are lack in S. triostegus .The result showed that three types of ganglion cells, long, medium and small as well as there is additional type called Giant ganglion cell found in L. abu .The head of optic nerve has multiple papillae in S. triostegus , while it is smooth in L. abu